2012
DOI: 10.1073/pnas.1207662109
|View full text |Cite
|
Sign up to set email alerts
|

Self-monitoring of social facial expressions in the primate amygdala and cingulate cortex

Abstract: Keeping track of self-executed facial expressions is essential for the ability to correctly interpret and reciprocate social expressions. However, little is known about neural mechanisms that participate in self-monitoring of facial expression. We designed a natural paradigm for social interactions where a monkey is seated in front of a peer monkey that is concealed by an opaque liquid crystal display shutter positioned between them. Opening the shutter for short durations allowed the monkeys to see each other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 50 publications
2
54
0
Order By: Relevance
“…Most importantly, these results pave the way for future experiments that will replace videos with live interactions with conspecifics as already pioneered by a few laboratories. 70,78,81,82 The ideal development would be to implement in the laboratory closed-loop social interactions. The social brain evolved to process social signals and make social decisions in closed-loop interactions—and neural activity monitored under such conditions holds the promise of further exciting discoveries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most importantly, these results pave the way for future experiments that will replace videos with live interactions with conspecifics as already pioneered by a few laboratories. 70,78,81,82 The ideal development would be to implement in the laboratory closed-loop social interactions. The social brain evolved to process social signals and make social decisions in closed-loop interactions—and neural activity monitored under such conditions holds the promise of further exciting discoveries.…”
Section: Resultsmentioning
confidence: 99%
“…Neural responses to tactile stimuli in the primate amygdala have not been previously reported and understanding their function will require further exploration. These neurons may serve as necessary sensory feedback during the production of facial expressions, as suggested by Livneh et al 70 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, subcortical connections of the rostral ACC include midline, intralaminar and mediodorsal nuclei , and the lateral and accessory basal nuclei of the amygdala (Ghashghaei and Barbas, 2002;Morecraft et al, 2007). Note that monkey studies showed that neurons in both the anterior cingulate cortex and amygdala respond during production of lip-smacking, that is a typical monkey emotional and affiliative facial expression (Livneh et al, 2012). On the basis of this evidence, Gothard (2014) suggested that this region is in position to coordinate both the behavioral and autonomic expression of emotions.…”
Section: Localization Of Es-evoked Laughtermentioning
confidence: 97%
“…shown by single neuron studies (Livneh et al, 2012), and on the other side that rostral ACC, ventral insula and the amygdala are part of the same cortico-subcortical loop (Höistada and Barbas, 2008), one can speculate that they constitute the core structures for the control of positive emotions.…”
Section: An Anatomical Network For Laughmentioning
confidence: 98%
“…Macaques, in particular, exhibit prototypical facial movements associated with specific types of vocalizations [82]. Both the pre-frontal mirror neuron system [83] and anterior cingulate cortex [84] exhibit neural activities that reflect an animal’s current facial gestures, making them two possible sites for non-auditory vocal self-monitoring. Further work will be needed to elucidate the role of these pathways in vocalization-associated somatomotor control and in the integration of multiple sensory pathways for feedback vocal control.…”
Section: Sensory-motor Mechanisms and Self-monitoringmentioning
confidence: 99%